2017
DOI: 10.1108/ijse-01-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Reckoning females’ education as a determinant of fertility control in Pakistan

Abstract: Purpose The purpose of this paper is to obtain empirical evidence on the impacts of socio-economic and demographic factors on the fertility decisions taken by a common family in developing countries like Pakistan. Also, this study contravenes the conventional orthodoxy of childbirth decisions of a family by enlarging the canvas and conjectures the fundamental nexus amongst female’s education, fertility and contraceptive use. Design/methodology/approach The study is based on micro-level data, obtained from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Results suggest that being uneducated, poor, residing in rural areas, and having no children decreased the likelihood of using modern contraceptives among adolescents. This was found to be similar to previous studies that have identified the role of socio-demographic characteristics as facilitators and barriers for uptake of modern contraceptive use among adolescents [ 27 – 29 ]. Poor and less educated adolescent girls have been found to have limited autonomy, knowledge, and awareness about contraceptive use [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…Results suggest that being uneducated, poor, residing in rural areas, and having no children decreased the likelihood of using modern contraceptives among adolescents. This was found to be similar to previous studies that have identified the role of socio-demographic characteristics as facilitators and barriers for uptake of modern contraceptive use among adolescents [ 27 – 29 ]. Poor and less educated adolescent girls have been found to have limited autonomy, knowledge, and awareness about contraceptive use [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…Third, total population of Pakistan was approximately 188 million in 2014, which increased to 193.85 million in 2016. Despite the continued population planning, Pakistan will be the sixth highly populated country of the world and it is predicted to reach around 342 million by 2050 at the recent consensus (Sheikh, Sadaqat, & Meraj, 2014). According to Pakistan Bureau of Statistics 2016, total population of Pakistan between the age group of 25 and 54 years range approximately 7.45 million and the median age is 23.4.…”
Section: Why Pakistan?mentioning
confidence: 99%
“…These findings go in tune with previous studies which have acknowledged the importance of socioeconomic factors as facilitators and barriers to the uptake of modern contraceptive use among adolescents. [25][26][27] Another important socioeconomic factor affecting contraceptive use was religion. Respondents from Muslim and Other religions showed a low preponderance of using contraception.…”
Section: Discussionmentioning
confidence: 99%